Barriers and facilitators for the utilisation of psycho-oncological services in German hospitals as perceived by patients and healthcare professionals: a mixed-methods study - Liv Betker; Kristina Buch; Pia Berlin; Anna J. Pedrosa Carrasco; Jorge Riera Knorrenschild; Carola Seifart; Pia von Blanckenburg (BMC Health Services Research)
Abstract Background Psycho-oncological services (POS) are an integral and widely recommended part of comprehensive cancer care. However, their utilisation appears to fall short of the perceived need. This study aimed to explore barriers and facilitators for the uptake of POS in the context of existing clinical structures and pathways to POS. Methods A mixed-methods study was conducted, drawing on elements of a Delphi approach, including an iterative two-round feedback process and an expert panel. The expert panel consisted of healthcare professionals in cancer care (n = 27) and cancer patients (n = 14). The first round comprised open-ended questions to explore different perspectives related to the research question. The resulting material was analysed qualitatively and grouped into themes, which were rated according to their perceived importance by the expert panel in the second survey-round (N = 27). Results The expert panel identified 69 aspects influencing the uptake of POS; 81% were rated as relevant in the second round. They were grouped into structural factors at hospital level, aspects related to internal processes, and factors at patient level. Central aspects were recommendations of POS by the clinical staff, personal introduction of the psycho-oncologist, integration and acceptance of POS within the hospital organisation, information dissemination about POS to both patients and clinical staff, and the possibility of flexible access routes to POS since patients’ preferences differed. Patient-groups more difficult to reach with a POS-offer were also identified. Conclusion The results can be used to review implemented clinical pathways to POS in diverse hospital contexts, helping to identify and improve critical aspects accordingly, and thus improve service accessibility. Trial registration This study was pre-registered at the German Clinical Trials Register (DRKS-ID: DRKS00025105; registration date: 26-05-2021).